Caveolin-1 expression in different types of psoriatic lesions: Analysis of 66 cases - Feng Zhang; Heyu Li; Yicheng Zhou; Yunhe Gu; Lifeng Wang (Wolters Kluwer Medknow Publications, 2014)
Background: Caveolin-1 is a key structural and functional protein. Caveolin-1 is known to modulate multiple signal-transducing pathways involved in cell differentiation and proliferation. Psoriasis is viewed as a multifactorial pathology characterized by keratinocyte hyperproliferation and abnormal cell maturation. Objectives: To examine the expression of caveolin-1 in skin biopsies from normal subjects, patients, and subjects with the three respective isoforms of psoriasis (psoriasis vulgaris, localized pustular psoriasis, and erythrodermic psoriasis). The expression level of caveolin-1 was compared among psoriasis vulgaris, localized pustular psoriasis, erythrodermic psoriasis, and normal subjects. Materials and Methods: Using immunohistochemical methods, caveolin-1 protein expression was assayed in four groups. An analysis was conducted on skin samples obtained from 22 normal subjects and 28 patients with psoriasis vulgaris, 22 patients with localized pustular psoriasis, and 16 patients with erythrodermic psoriasis. The statistical analysis of the scoring criteria reﬂecting the level of Caveolin-1 immunostaining between different groups was determined using the Mann-Whitney U-test. Results: In the normal skin, intense and consistent caveolin-1 staining was present in 22 cases. The Caveolin-1 protein was signiﬁcantly reduced and showed very weak or absent staining within the tissues of psoriasis vulgaris, localized pustular psoriasis, and erythrodermic psoriasis (respective P < 0.001). Caveolin-1 protein expression in psoriasis vulgaris was higher than that in localized pustular psoriasis and erythrodermic psoriasis (respective P < 0.05). Caveolin-1 protein expression was no different in localized pustular psoriasis and erythrodermic psoriasis (P > 0.05). Conclusion: The ﬁnding of this study was consistent with a downregulation of Caveolin-1, which might serve as an etiological factor in the development of psoriasis vulgaris, localized pustular psoriasis, and erythrodermic psoriasis. Further mechanistic investigations are required to prove that Caveolin-1 protein has the potential and may be a novel target for therapy of psoriasis vulgaris, localized pustular psoriasis, and erythrodermic psoriasis.